Dependência do Estado como barreira à emancipação dos pequenos produtores assentados no Perímetro Irrigado de Maniçoba (Juazeiro-BA) - Mendonça, Selvina da Costa (2006)
This work notices the transformations occurred in rural areas of the sub-médio San Francisco River and it analyses the development of irrigated agricultural perimeters since the implementation of public projects of irrigation in the region by Codevasf. Those public projects focus on the process of transference of management to small farmers and the factors that interfere in these processes. Some difficulties arise from the relationship Codevasf and small farmer workers. To solve them, reference was taken from the proposal of work of emancipation programs elaborated by the Ministério da Integração Nacional that guides the work done by Codevasf. In this study, we try to comprehend the complexity of practices of different actors involved in the relationship between those parties and their effects in the internal dynamism of irrigated perimeters. We made reference on how this process is done in the access to the land in Brazil since the first occupations up to the present moment and the importance of the role of the Lei de Irrigação. Also, the vital role of the San Francisco River was observed when the implementation of public policies in the agricultural development of the San Francisco Valley through programs of settlement of small farm workers in irrigated areas. It was tried to understand the web that involves the irrigated perimeters. The principal part of the analyses was done in the Maniçoba Project in Juazeiro Bahia for it is the perimeter where most of the time was spent on professional practices. Codevasf still works in a paternal way in relation to the farmers and political interference is still done which creates a dependence from the part of the producers and their organizations. To reverse this situation, it is necessary that Codevasf take the decision to set itself apart from the management of the irrigated perimeters and it should put into practice the needed actions to overcome obstacles that have put the effectiveness of its emancipation in order to make agricultural workers responsible for their own acts.